2016
DOI: 10.1038/srep39485
|View full text |Cite
|
Sign up to set email alerts
|

Associations of five polymorphisms in the CD44 gene with cancer susceptibility in Asians

Abstract: CD44 polymorphisms have been previously associated with cancer risk. However, the results between independent studies were inconsistent. Here, a meta-analysis was performed to systematically evaluate associations between CD44 polymorphisms and cancer susceptibility. A comprehensive literature search conducted in PubMed, Embase, and Web of Science databases through August 10, 2016 yielded 11 eligible publications consisting of 5,788 cancer patients and 5,852 controls. Overall, odds ratios (OR) calculated with 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Several SNPs of CD44 have been reported to have significant correlations with the risk of various cancers in Asians [20,32]. The rs10836347 C/T polymorphism is associated with a higher risk of hepatocellular carcinoma in individuals who consume alcohol [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several SNPs of CD44 have been reported to have significant correlations with the risk of various cancers in Asians [20,32]. The rs10836347 C/T polymorphism is associated with a higher risk of hepatocellular carcinoma in individuals who consume alcohol [33].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that CD44 polymorphisms are a risk factor for susceptibility to different cancers [14][15][16][17][18][19][20]. However, the role of CD44 polymorphisms in the clinicopathological characteristics of lung adenocarcinoma is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a cohort of 279 patients with lung adenocarcinoma, both CD44 rs713330 T/C and rs10836347 C/T polymorphisms exhibited significant associations with tumor size and invasion, independent of EGFR mutational status [77].…”
Section: Cd44 Polymorphisms and Cancer Riskmentioning
confidence: 99%